Impact of Admission Hyperglycemia on Outcomes of Patients With Acute ST-Elevation Myocardial Infarction - Ali, Kenan (Latakia University Journal -Medical Sciences Series, 2020)
Objective: the present study aims to evaluate the impact of admission hyperglycemia on short-term outcomes in patients admitted with ST- elevation myocardial infarction (STEMI). Methods and Patients: Consecutive patients with STEMI admitted to our Coronary Care Unit (CCU) between February 2018 and January 2019 were enrolled in the study. Patients were divided into two groups based on admission glucose level, Group1 (n=60) patients with hyperglycemia ≥200 mg/dl, Group2 (n=88) patients without admission hyperglycemia <200 mg/dl, and their short-term outcomes were compared. Results: A total of 148 patients were included , Mean age was 60.14 ± 12.68 years in (Group 1) versus 54.92 ± 11.4 years in (Group2), P=0.01 and 107(72.29%) were male, hyperglycemia was detected in 60(40.5%) of the patients . In Univariate analysis, patients Group1 were more likely to experience acute heart failure (38.3% vs. 7.9%, P<0.001), Cardiogenic shock (28.3% vs. 1.1%, P<0.001), and mortality (26.6% vs. 1.1% P<0.001). In Multivariate regression analysis hyperglycemic remains prognostic factor for mortality (OR : 2.7, 95% CI : 2-6.3 , p=0.04) and acute heart failure (OR:7.2,CI95%:2.8-18.2,p=0.0001). Conclusion: Hyperglycemia at admission is a bad prognostic factor for mortality and acute heart failure in patients with STEMI. الهدف: تهدف الدراسة الحالية الى تقييم تاثير فرط سكر الدم عند القبول لدى المرضى المقبولين بقصة احتشاء عضلة قلبية حاد عابر للجدار الطرق والرضى: تم دراسة جميع المرضى المقبقولين في وحدة العناية المشددة بقصة احتشاء عابرللجدار بين شباط2018 وكانون الثاني 2019 تم تقسيم المرضى الى مجموعتين بناء على قيمة سكر الدم عند القبول،المجموعة الاولى(60مريض) وهي مجموعة فرط سكرالدم عند القبول (<200ملغ/دل)والمجموعة الثانية(88مريض)وهي المجموعة بغياب فرط سكرالدم عند القبول(>200ملغ/دل) تم متابعة المرضى خلال فترة الاستشفاء والمقارنة بينهما ا النتاىج:تبين في التحليل احادي البيانات ان مرضى فرط سكر الدم عند القبول كان لديهم معدل وفيات اعلى بالمقارنة مع مرضى سكر الدم غير المرتفع عند القبول(26%vs.1.1%0.000.1>p التحليل متعدد البيانات اظهر ان سكر الدم المرتفع عند القبول كان عامل خطرمستقل للوفيات عند مرضى الاحتشاء العابر للجدار(0,04=p,6,3-2:ci %95,2:7:or) الخلاصة: فرط سكر الدم عند القبول عامل خطر مستقل للوفيات عند مرضى احتشاء العضلة القلبية الحاد العابرللجدار